The Global Horizon Expectations of Migration in Africa and the Middle East - Graw, Knut; Schielke, Samuli (Leuven University Press, 2021)
Although contemporary migration in and from Africa can be understood as a continuation of earlier forms of interregional and international migration, current processes of migration seem to have taken on a new quality. This volume argues that one of the main reasons for this is the fact that local worlds are increasingly measured against a set of possibilities whose referents are global, not local. Due to this globalization of the personal and societal horizons of possibilities in Africa and elsewhere, in many contexts migration gains an almost inevitable attraction while, at the same time, actual migration becomes increasingly restricted. Based on detailed ethnographic accounts, the contributors to this volume focus on the imaginations, expectations, and motivations that propel the pursuit of migration. Decentring the focus of much of migration studies on the 'receiving societies', the volume foregrounds the subjective aspect of migration and explores the impact which the imagination and practice of migration have on the sociocultural conditions of the various local settings concerned. that happens between text and context when works of children's literature are translated. What contexts of production and reception account for how translated children's books come to be made and read as they are? How are translated children's books adapted to suit the context of a new culture? Spanning the disciplines of Children's Literature Studies and Translation Studies, this book brings together established and emerging voices to provide an overview of the analytical, empirical and geographic richness of current research in this field and to identify and reflect on common insights, analytical perspectives and trajectories for future interdisciplinary research. This volume will appeal to an interdisciplinary audience of scholars and students in Translation Studies and Children's Literature Studies and related disciplines. It has a broad geographic and cultural scope, with contributions dealing with translated children's literature in the United Kingdom, the United States, Ireland, Spain, France, Brazil, Poland, Slovenia, Hungary, China, the former Yugoslavia, Sweden, Germany, and Belgium.